All-cause mortality, cardiovascular events, and health care costs after 12 months of dual platelet aggregation inhibition after acute myocardial infarction in real-world patients: findings from the Platelet-aggregation Inhibition: Persistence with treatment and cardiovascular Events in Real world (PIPER) study. - Esposti, Luca Degli; Perrone, Valentina; Veronesi, Chiara; Buda, Stefano; Rossini, Roberta; Degli Esposti, Luca (Vascular Health & Risk Management, 2018)
Objectives: The aim of the study was to assess all-cause mortality and cardiovascular (CV) events in patients after a period of 12 months of treatment with dual antiplatelet therapy (DAPT) after hospitalization for acute myocardial infarction (AMI) in a real-world setting. Health care costs for the management of patients post-AMI was also assessed.Methods: A retrospective analysis using data from the administrative databases of six local health units (LHUs) was performed. All beneficiaries of these LHUs hospitalized with AMI between January 01, 2010, and December 31, 2011, and exposed to a treatment period with DAPT up to 12 months after AMI discharge were included. All-cause mortality, CV hospitalizations, and health care costs occurring during the 36-month follow-up period from end of treatment with DAPT were considered. For the cost analysis, only patients still alive at the end of the follow-up period were included.Results: A total of 2,721 patients were included (mean ± SD age 63.6±17.3 years, 67.8% males). About 17% and 18% of all patients had CV events and died during the follow-up period, respectively. The annual mean cost per patient was €3,523.27. During the follow-up period, 63 patients had a second AMI event; for whom, the mean health care cost per patient was €19,570.70.Conclusion: In a real-world setting in Italy, considering a 36-month follow-up period, all-cause mortality, CV events, and related health care cost of patients hospitalized with an AMI undergoing a 12-month treatment period with DAPT remained relevant. This study suggests that increased efforts aimed at the prevention of recurrent AMI are warranted, as well as an accurate risk stratification in order to improve long-term outcome.